Puri Kesiman: Saksi Sejarah Kejayaan Kerajaan Badung - Nyoman Wijaya (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
Puri Kesiman had has a strategic position that functioning as the headquarters of the struggle in the early twentieth century, since Kesiman involvement in “Puputan of Badung”, and the Indonesian independence struggle on Bali. As the only remaining palace of the King of Badung until now, it will be interesting to study how the Puri of Kesiman can survive long enough and its action in the present. Especially in relation to the position and role of the palace (puri) in Balinese society, especially in the increasingly pluralistic Village Kesiman where it is located. This study discusses the history of the Castle Kesiman, Kesiman Puri’s role in the history of Bali general and history of Badung particular; and traces the position of Puri Kesiman in early independence era till today.